2019
DOI: 10.1021/jacs.9b00248
|View full text |Cite
|
Sign up to set email alerts
|

Linear Supramolecular Polymers Driven by Anion–Anion Dimerization of Difunctional Phosphonate Monomers Inside Cyanostar Macrocycles

Abstract: Supramolecular polymers have enabled far-reaching fundamental science and the development of diverse macromolecular technologies owing to the reversible and noncovalent chemical connectivities that define their properties. Despite the unabated development of these materials using highly tailorable recognition elements, anion-based polymers remain rare as a result of the weak interactions they mediate. Here, we use design rules inspired by cation-driven polymers to demonstrate a new noncovalent link based on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 73 publications
5
78
0
Order By: Relevance
“…Flood et al reported the self-assembling behavior of dodecanediyl-bis phosphonic acid without the trans-P-C C moiety in organic solvents. They revealed that this compound formed a linear supramolecular polymer via intermolecular hydrogen bonding of the phosphonic acid moieties 28 . These results suggest that introduction of the trans-P C C moiety significantly increases the hydrophilicity, while the two trans-P C C moieties at both ends of BPC 12 may induce dense packing via hydrogen bond interactions.…”
Section: Surface Activity and Self-assembling Propertiesmentioning
confidence: 99%
“…Flood et al reported the self-assembling behavior of dodecanediyl-bis phosphonic acid without the trans-P-C C moiety in organic solvents. They revealed that this compound formed a linear supramolecular polymer via intermolecular hydrogen bonding of the phosphonic acid moieties 28 . These results suggest that introduction of the trans-P C C moiety significantly increases the hydrophilicity, while the two trans-P C C moieties at both ends of BPC 12 may induce dense packing via hydrogen bond interactions.…”
Section: Surface Activity and Self-assembling Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Polyrotaxanes, in which many macrocycles are threaded onto a polymer chain and trapped by terminal bulky stoppers, have recently attracted considerable interest for their simple structures and properties different from conventional polymers. [8][9][10][11][12][13] Poly(ethylene oxide)s (PEOs) are a class of polymers, which exhibit crystalline and thermoplastic behavior, as well as high solubility in both water and organic solvents. PEOs have a broad scope of applications in materials science and biochemistry because of their excellent biological compatibility and commercial availability in a wide range of molecular weights.…”
Section: Introductionmentioning
confidence: 99%
“…This method of assembly allows for some forms of molecular motion, which endows these materials with unique mechanical and thermal properties [1–7] . Polyrotaxanes, in which many macrocycles are threaded onto a polymer chain and trapped by terminal bulky stoppers, have recently attracted considerable interest for their simple structures and properties different from conventional polymers [8–13] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While AEHB interactions have been identified in solid-state crystal structures, detection of unchaperoned anion dimers or oligomers in solution is challenging due to limited spectroscopic signatures, weak anion–anion bonds, labile protons, and rapidly exchanging bound species. These difficulties can be attenuated by the use of an anion-binding host to template AEHB interactions, 17 leading to reports of HSO 4 – dimers 15 , 18 and H 2 PO 4 – dimers 19 and oligomers 20 , 16 in solution. Conductimetric and spectroscopic techniques have shown the formation of AEHB dimers of HCO 3 – and H 2 PO 4 – in water 21 or DMSO 22 and suggested the possibility of higher order oligomers.…”
Section: Introductionmentioning
confidence: 99%